2021
DOI: 10.3390/ijms22105274
|View full text |Cite
|
Sign up to set email alerts
|

Viral Interactions with Adaptor-Protein Complexes: A Ubiquitous Trait among Viral Species

Abstract: Numerous viruses hijack cellular protein trafficking pathways to mediate cell entry or to rearrange membrane structures thereby promoting viral replication and antagonizing the immune response. Adaptor protein complexes (AP), which mediate protein sorting in endocytic and secretory transport pathways, are one of the conserved viral targets with many viruses possessing AP-interacting motifs. We present here different mechanisms of viral interference with AP complexes and the functional consequences that allow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 230 publications
(283 reference statements)
0
6
0
1
Order By: Relevance
“…Intracellular trafficking is used by viruses to mediate their entry into host cells or Comment [SJ5]: Reviewer 1, comment 2. "The authors are suggested to introduce the AP roles in the cell in detail according to the figures which would help readers understand the manuscript" for AP5 promote their replication [270]. A deficiency in intracellular transport can cause severe genetic diseases [271] while it is also putatively a target for treating cancer [272].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Intracellular trafficking is used by viruses to mediate their entry into host cells or Comment [SJ5]: Reviewer 1, comment 2. "The authors are suggested to introduce the AP roles in the cell in detail according to the figures which would help readers understand the manuscript" for AP5 promote their replication [270]. A deficiency in intracellular transport can cause severe genetic diseases [271] while it is also putatively a target for treating cancer [272].…”
Section: Discussionmentioning
confidence: 99%
“…Clathrin [277] LLNLD [277] μ1 HIV-Nef [278] YXXØ, X is any amino acid, Ø is a bulky hydrophobic amino acid [270,279];…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations